(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The distribution of Cu2+ between buffered aqueous phases and chloroform solutions of 4,4´-(1E,1E´)-1,1´-(ethane-1,2-diylbis(azan-1-yl1ylidene))bis(5-methyl-2-phenyl-2,3-dihydro-1H-pyrazol-3-ol) (H2BuEtP) alone and in the presence of 1-(3-hydroxy-5-methyl-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl) butan-1-one(HBuP) was investigated using solvent-solvent extraction. 200 mgL-1 Cu2+ was used for the study with an equilibration time of 60 minutes. Concentration of Cu2+ in aqueous phases after equilibration was determined with AAS and calculated by difference between Copper concentration in the aqueous phases and the organic phases, and distribution ratios(D) and percentage extractions(%E) were determined. Slope analysis from plots of log D against buffers pHs, ligands concentrations and metal concentrations were used to propose distribution reaction equations and extracted Cu2+ complexes as Cu(HBuEtP.X)(o) for ligand alone and Cu(HBuEtP.BuP)(o) in the presence of HBuP. The extraction constant log Kex, obtained for H2BuEtP (-5.11±0.7) was greater than that for H2BuEtP/HBuP (-12.94±1.26) which indicated HBuP did not exert any synergic effects in the distribution of Cu2+, even though partition coefficient log D for H2BuEtP/HBuP of 2.03 ± 0.81 was > 0.97 ± 0.62 for H2BuEtP. Comparing results with those of other studies, showed carbon chain length of structurally related ligands effects on metal ions distribution is dependent on the particular metal ion. The ligand H2BuEtP was a better extractant for Cu2+ than Ni2+ and Fe2+ only as the results for Pb2+, UO2+ and Cd2+ were better based on log Kex values.